A Negative-Stranded RNA Virus Infecting Citrus Trees: The Second Member of a New Genus Within the Order Bunyavirales - Navarro, Beatriz; Zicca, Stefania; Minutolo, Maria; Saponari, Maria; Alioto, Daniela; Di Serio, Francesco (Frontiers in Microbiology, 2018)
A new RNA virus has been identified from a sweet orange tree in southern Italy. This virus, tentatively named citrus virus A (CiVA), has a bipartite genome composed of i) a negative-stranded (ns) RNA1, encoding the viral RNA-dependent RNA polymerase (RdRp), and ii) an ambisense RNA2, coding for the putative movement protein (MP) and nucleocapsid protein (NP), with the two open reading frames separated by a long AU-rich intergenic region (IR) adopting an hairpin conformation. CiVA genomic RNAs and the encoded proteins resemble those of the recently discovered citrus concave gum-associated virus (CCGaV). This CCGaV, a nsRNA virus associated with the ancient citrus concave gum disease, has been proposed as the representative member of a new genus tentatively named Coguvirus. Molecular and phylogenetic analyses presented here support the classification of CiVA, and likely of other two recently described nsRNA viruses infecting plants, in this new genus. By showing that the evolutionary origin of the MP of all the putative coguviruses likely differs from that of their respective RdRp and NP, this study also provides evidence of a likely modular genome evolution for these viruses. Moreover, phylogenetic data support the proposal that, during the evolutionary history of nsRNA viruses, the plant-infecting viruses most likely emerged from an invertebrate-infecting ancestor several times as independent events. CiVA was identified in a field sweet orange tree not showing any obvious symptom and was graft-transmitted to sweet orange, grapefruit, rough lemon and Dweet tangor indicator plants that did not developed symptoms. The capacity of infecting citrus hosts of several species was also confirmed by a preliminary survey that identified orange, mandarin, clementine and lemon trees as natural hosts of CiVA in several fields of southern Italy, again without any obvious association with specific symptoms.